The promotion of mature theory of mind skills in educational settings: a mini-review - Bianco, Federica; Castelli, Ilaria (Frontiers in Psychology, 2023)
After formal school entry, theory of mind development encounters a blooming period of growth intertwined with social and academic achievements and challenges. Within this framework, in last years researchers have proposed training programs to foster mature ToM skills, but also, to test causal pathways for the role that ToM development may have in broader cognitive and social outcomes. In the current mini-review we examine which training programs have been developed so far to enhance three key aspects of Mature ToM Skills: second-order false belief reasoning, the ability to put one’s own ToM knowledge into use, and the mentalization of thoughts and emotions. We also illustrate effects of these activities on intra- and inter- personal competence. In its conclusions the paper provides considerations of both first achievements of research in this area and gaps to be addressed in future works.